2007
DOI: 10.1111/j.1741-2358.2007.00183.x
|View full text |Cite
|
Sign up to set email alerts
|

Tooth loss and associated factors in long‐term institutionalised elderly patients

Abstract: General health problems as well as a poor oral condition were significant risk indicators for tooth loss among the long-term institutionalised elderly. This suggests that the number of remaining teeth has a strong effect on oral health-related quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
53
5
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 20 publications
(29 reference statements)
7
53
5
2
Order By: Relevance
“…Th e incidence of edentulous persons among the institutionalized elderly found in this study was close to 45.3% found by Kraljevic et al 36 . Our fi ndings were lower compared to those obtained by De Visschere et al, who found that about two-thirds of the institutionalized elderly (64%) were edentulous 37 , but higher than 26.9% reported by Tramini et al 38 . Th e DMFT index of 24.08 among institutionalized elderly (Table 3) was lower than 26.6 found among institutionalized elderly in Canada 35 and 30.75 found in Slovenia 39 .…”
Section: Discussioncontrasting
confidence: 56%
“…Th e incidence of edentulous persons among the institutionalized elderly found in this study was close to 45.3% found by Kraljevic et al 36 . Our fi ndings were lower compared to those obtained by De Visschere et al, who found that about two-thirds of the institutionalized elderly (64%) were edentulous 37 , but higher than 26.9% reported by Tramini et al 38 . Th e DMFT index of 24.08 among institutionalized elderly (Table 3) was lower than 26.6 found among institutionalized elderly in Canada 35 and 30.75 found in Slovenia 39 .…”
Section: Discussioncontrasting
confidence: 56%
“…Similar findings can also be found in LTC residents. Tramini and colleagues found that among 321 long-term care residents, more than 50% had lost 21 or more teeth at the time of examination [13]. A recent study also found that among 260 NH residents, the mean number of functioning teeth was only 10.6, indicating remarkable oral function loss in these individuals [11].…”
Section: Introductionmentioning
confidence: 99%
“…The women were more and older than the men (Table 1). In spite of the high level of dependency explained by their important cognitive diseases, the participants of this study were younger than the patients usually hospitalized in long term units [15][16].…”
Section: Discussionmentioning
confidence: 99%
“…A similar population (institutionalized old patients with moderate to severe cognitive decline) shows a more damage dental status than the studied population who is younger and has been undergone periodic oral aftercares during their life [15][16].…”
Section: Quantitative Oral Statusmentioning
confidence: 99%
See 1 more Smart Citation